CHALLENGES OF REGIONAL GOVERNMENT IN IMPLEMENTING REGIONAL AUTONOMY IN INDONESIA - Verdico Arief; Andjani Trimawarni; Muhammad Rachimoellah (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Since the 1998 reforms, 12 new provinces have been established in Indonesia. Currently, in 2025 Indonesia has 38 provinces. The establishment of these new autonomous regions aims to accelerate development, ensure equitable distribution, and improve public welfare. However, many new autonomous regions have failed to achieve these goals, and their presence has become a burden on the central government because they are deemed incapable of developing independently. This study attempts to examine the factors that hinder the independent development of new autonomous regions. This study used a systematic literature review technique. The results revealed that the majority of problems experienced were due to limited resources. This issue was still found even though these new autonomous regions had previously conducted academic studies to assess their feasibility. Consequently, the central government of the Republic of Indonesia had to provide subsidies to support the operational activities of these autonomous regions.